Thunkable – a free application to develop phone apps / Dr Tuan Sarifah Aini Syed Ahmad and Nor Haniza Hasan - Syed Ahmad, Tuan Sarifah Aini; Hasan, Nor Haniza (UiTM Cawangan Negeri Sembilan, 2022)
Many instructors have limitations such as budget, time and information and communication technology (ICT) skills to develop phone apps. Therefore, they are reluctant to develop specific phone apps that may meet their students' learning needs. Currently, many applications are available for developing phone apps faster with a minimum budget. The applications do not require coding (a computer language to develop codes). Therefore, instructors with limited ICT skills can still have the opportunity to build phone apps. The development requires the users to drag and drop objects and blocks to design the interactivity of the objects. Thunkable is one of the applications available for instructors to develop phone apps. Instructors can develop phone apps online at https://thunkable.com/. They can sign up for free to create an account using a Google account, Apple account or an email.